Pubertal Development Measurement in Children with and without Autism Spectrum Disorder: A Comparison Between Physical Exam, Parent- and Self-Report - Corbett, Blythe A. (J Autism Dev Disord, 2019)
Adolescence is a time of remarkable biopsychosocial change, which may be particularly challenging for youth with autism spectrum disorder (ASD), necessitating enhanced understanding and accurate assessment of pubertal maturation. The study compared physical examination to parent- and self-report measures in 200 participants (134 males and 66 females) ages 10.0–13.5-years. Both participants with typical development (TD; n=78) and ASD (n=122) were included. Concordance ranged from slight-to-fair for self-assessments (κ=.17–.32) and slight-to-moderate for parent-report (κ=.21–.44). Concordance of physical exam with self- and parent-report of the ASD group was somewhat lower than for the TD group. Findings indicate pubertal assessments by parent or child are not reliable indices of precise pubertal staging.